TEACHING ENGLISH VOCABULARY USING SONGS TO DEVELOPING STUDENTS’ VOCABULARY MASTERY - Bawawa, Marni (Kajian Linguistik, 2020)
The purpose of this research is to find out whether songs can develop students vocabulary mastery or not and to find out whether songs can increase of students’ interest to develop the students’ vocabulary mastery in second grade students at SMP Negeri 3Merauke or not. The subjects in this research were second grade students at SMP Negeri 3 Meraukeconsisting of 30 students. This research was classified into qualitative descriptive research. The researcher was used pretest and posttest design and conclude the data using two instrument; vocabulary test and then questionnaire. Vocabulary test to measure development in the English vocabulary mastery, the test is multiple-choice test. While the questionnaire to find out the students attitude toward the using songs in teaching English vocabulary. The questionnaire test consist of 5 questions. Based on the results of vocabulary tests on pretest and posttest, there was significant development. This can be seen on the percentage value of each test. The percentages of pretest was 40.66%, while on the posttest increased namely 87.83%. It means that using songs can develop students 'vocabulary mastery at grade VIII in SMP Negeri 3Merauke and the students' are more interest in learning English vocabulary by using songs than without using songs. It can be proved from the results of the questionnaire that most of the students’ said that the using songs could help them to increase their interested in learning process.Kewords; songs, develop, vocabulary, mastery